High-Yield Recovery of Antioxidant Compounds from Bambusa chungii Culms Using Pressurized Hot Water Extraction - Xianshuang Cao; Yaoyao Zhang; Hang Xun; Jin Wang; Feng Tang (MDPI AG, 2022)
A large amount of waste from Bambusa chungii culms is generated from the bamboo pulping industry, causing disposal problems. Nevertheless, bamboo culms are a suitable source of functional ingredients, such as antioxidant compounds. However, because of the high compactness and tightness in their material structure, obtaining phytochemicals from bamboo culms using conventional organic solvent extraction methods can be inefficient. In this research, we developed a pressurized hot water extraction (PHWE) method to recover 19 target phenolic compounds from Bambusa chungii culms. The extracted compounds were determined by ultra-high performance liquid chromatography-quadrupole time-of-flight-mass spectrometry (UPLC-QTOF-MS). The antioxidant potential of the extracts was evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and ferric reducing antioxidant power (FRAP) assays. We investigated the effects of temperature, extraction time, and the material-to-liquid ratio on PHWE, and these parameters were optimized with a Box-Behnken design experiment and response surface tool. The optimal extraction condition was found at 170 °C, with a 1:30 g/mL material-to-liquid ratio and a 14 min extraction time. Following these optimal parameters, the total yield of target phenolic compounds (TYPC) reached 3.85 mg/g of raw material, and the half-maximal inhibitory concentrations (IC50) for the DPPH and ABTS tests were 94.7 mg/L and 21.88 mg/L, respectively. The FRAP value was 1.23 μmol FSE/mg of dried extract. A strong correlation between TYPC and the antioxidant activity of the extract was confirmed. The TYPC and antioxidant capacity of the optimal PHWE extract of the Bambusa chungii culms were both considerably higher than those of extracts obtained from conventional solvent extractions. These results indicated that PHWE is an excellent green technique for recovering phenolic compounds from bamboo culms, and the PHWE extracts of Bambusa chungii culms may be a good source of natural antioxidants.